Tourism Industry Supply Chain through Stakeholder Participants: Facing Environment Uncertainty of Post Pandemic Covid-19 - Achmad, Fandi; Sriwana, Iphov Kumala; Prambudia, Yudha; Rumanti, Augustina Asih (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
The environmental uncertainty due to the COVID-19 pandemic poses severe challenges for all parts of the supply chain in the tourism industry. The focus of the Indonesian government is to improve the condition of the tourism industry, which has experienced a decline in the number of tourists due to the COVID-19 pandemic. A supply chain tourism industry framework was developed through the Support System Facilities (SSF) variable to map the actors in the tourism industry activities in an uncertain environment due to COVID-19. The method in this study uses a qualitative descriptive approach through in-depth interviews, direct observation, and literature study. The results of this study are the tourism industry supply chain conceptual framework which states that there are several stages in distributing services and support systems and facilities to tourists, namely through suppliers, tour operators, tour agencies, and tourists. This finding has practical implications for the government in making a policy strategy.